1991
DOI: 10.1128/jcm.29.10.2209-2212.1991
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rubella virus immunoglobulin G (IgG) and IgM antibodies in whole blood on Whatman paper: comparison with detection in sera

Abstract: We compared detection of rubella virus hemagglutination inhibition (HI) antibody and rubella virus-specific immunoglobulin M (IgM) in dried whole blood spotted onto Whatman ifiter paper and serum samples, both of which were obtained from the same subject by venipuncture. Of 1,000 paired serum samples obtained to study HI antibodies, 807 dried blood samples had HI titers identical to those of the corresponding serum samples, and 193 dried blood samples showed 1 dilution difference. Storage of dried blood at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Overall, DBS and serum samples from 16,255 individuals were included: 13,742 (84.5%) adults, 560 (3.4%) 5-to 17-year old's and 2,082 (12.8%) less than five years old. Two studies reported antibodies against hepatitis A [14,15], nine hepatitis B [16][17][18][26][27][28]46,48,51], ten hepatitis C [19][20][21][22][26][27][28]37,46,48], eight HIV [23][24][25][26][27][28]46,50], three human papillomavirus (HPV) [29,30,37], three measles [31,32,42], three rubella [33,34,42], two syphilis [40,46], two H. pylori [35,47] and two malaria [38,49]. Twelve papers reported on Chagas disease [35], Epstein-Barr virus [36], HPV, H. pylori, hepatitis C and polyomavirus [37], Strong...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, DBS and serum samples from 16,255 individuals were included: 13,742 (84.5%) adults, 560 (3.4%) 5-to 17-year old's and 2,082 (12.8%) less than five years old. Two studies reported antibodies against hepatitis A [14,15], nine hepatitis B [16][17][18][26][27][28]46,48,51], ten hepatitis C [19][20][21][22][26][27][28]37,46,48], eight HIV [23][24][25][26][27][28]46,50], three human papillomavirus (HPV) [29,30,37], three measles [31,32,42], three rubella [33,34,42], two syphilis [40,46], two H. pylori [35,47] and two malaria [38,49]. Twelve papers reported on Chagas disease [35], Epstein-Barr virus [36], HPV, H. pylori, hepatitis C and polyomavirus [37], Strong...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twelve papers reported on Chagas disease [35], Epstein-Barr virus [36], HPV, H. pylori, hepatitis C and polyomavirus [37], Strongyloidiasis [39], pertussis [41], hepatitis E [56], Vibrio cholera [2], measles, mumps and rubella [42], tuberculosis and cytomegalovirus [43], toxoplasmosis [44], trypanosoma [45], Covid-19 [52], respectively. Twelve studies were conducted in Europe [14,18,21,27,29,30,35,[41][42][43]50,52], four in North America [19,20,32,36], eleven in South America [15][16][17]22,24,34,38,39,48,49,51], seven in Africa [23,25,26,31,40,44,45] and five in Asia [28,33,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These types of specimens are routinely collected from more than 95% of all newborns in the United States for screening of inborn errors of metabolism, and their performance is extremely well documented [U.S.D.H.H.S, 1998]. However, the use of ®lter paper blood spots to test for measles and rubella antibodies has been limited [Punnarugsa and Mungmee, 1991;Sanders and Niehaus, 1985;Wassilak et al, 1984;Khare et al, 1985;Condorelli et al, 1994Condorelli et al, , 1998de Souza et al, 1995;Veitorp and Leerhoy, 1981;de Swart et al, 2001]. Furthermore, this technique has been compared adequately with the detection by EIA of measles-speci®c IgM from serum samples only once [de Swart et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…DIA can be performed under field conditions because sophisticated laboratory equipment is not required, and the test is highly cost-effective (8,13). Serum or whole blood collected on filter paper is a convenient sample for serological assays (1,5,10,14). We used serum or whole blood collected on filter paper for the simultaneous detection of immunoglobulin G-class antibodies to measles virus, mumps virus, and rubella virus by DIA in order to discriminate between seropositive and seronegative individuals.…”
mentioning
confidence: 99%
“…The solution was filtered through a 0.22-,um-pore-size filter and stored in aliquots of 10 ml at -20°C. Prior to use, 10 ,ul of 3% H202 was added and the filters were incubated in this solution for 30 min. A visible red spot was considered a positive result.…”
mentioning
confidence: 99%